Life skills for 'real life': How critical thinking is contextualised across vocational programmes. Issue 3 (3rd July 2019) - Rönnlund, Maria; Ledman, Kristina; Nylund, Mattias; Rosvall, Per-Åke
ABSTRACT: Background : This article presents an analysis of how critical thinking is contextualised in everyday teaching in three vocational education and training (VET) programmes: Vehicle and transport, Restaurant and management, and Health and social care. Purpose : The main question addressed is: What knowledge discourses permeate different VET-contexts, and hence what kinds of opportunities for critical thinking do they offer students? Method : The qualitative analysis draws on data from a four-year ethnographic project exploring learning processes that can be characterised as civic education in Swedish vocational education. The analysis presented here used data collected during 85 days of observations of teaching in six VET classes, interviews with 81 students and 10 teachers, and collected teaching material. To explore why some contextualisations provided more opportunities and encouragement for critical thinking than others, we applied Bernsteinian concepts of 'horizontal and vertical knowledge discourses' and 'discursive gaps'. Findings and conclusions : Overall, teaching that was observed focused primarily on 'doing'. However, in all three programmes, the analysis identified that there were also situations that touched upon critical thinking. Three major themes were identified: critical thinking related to 'Personal experiences', 'The other(s)' and 'Wider perspectives'. It appeared that the frequency and nature of such situations varied with the knowledge discourses permeating the programme. Furthermore, we discuss the manifestations of critical thinking in relation to the wider context of what Bernstein refers to as pedagogic rights; individual enhancement, social inclusion and development of the competence and confidence to participate in political processes.